Race analysis of the men`s 50 m events at the 2021 LEN European Championships - Morais, J. E.; Barbosa, T. M.; Lopes, T.; Simbaña Escobar, D.; Marinho, D. A. (Sports Biomechanics, 2025)
The aim of this study was to: (i) characterise the stroke kinematics` stability of the male swimmers competing in the four 50 m events at the 2021 European Championships, and; (ii) understand the speed-time relationship in the four race events. All male swimmers who participated in the 50 m events (backstroke: 78 swimmers; breaststroke: 79 swimmers; butterfly: 89 swimmers; freestyle: 95 swimmers) were evaluated. In each swimming stroke swimmers were split in two groups (better and poorer performances). Significant variances (p < 0.05) were observed in both groups in all variables and for all swimming strokes. Swimming speed was the variable with the highest variance in both groups and strokes. Overall, better swimmers presented a low to high normative stability, and poorer swimmers a moderate-to-high. Speed-time curve fitting for all swimming strokes and groups suggested a cubic relationship. It can be considered that elite male swimmers racing 50 m sprint events at major competitions present an all-out trend. The present data provide coaches with substantial information about the main trend in the 50 m sprint events, specifically in each section of the race.